1995
DOI: 10.1051/rnd:19950403
|View full text |Cite
|
Sign up to set email alerts
|

Relationships between microflora and caecal fermentation in rabbits before and after weaning

Abstract: Summary ― Some microbiological and biochemical parameters of caecal content were studied in 15-to 49-d-old rabbits that were slaughtered sequentially. The ammonia level did not differ before weaning (11.5 mmol/L on average) (P= 0.41 ) or after weaning (7.4 mmol/L on average) (P= 0.19) but decreased by 40% (P < 0.001) between days 29 and 32. The level of pH decreased linearly (P < 0.001) throughout the period studied. The Escherichia coli counts decreased up to weaning (P < 0.001) and was then not signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

14
43
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 68 publications
(58 citation statements)
references
References 10 publications
14
43
1
Order By: Relevance
“…In conformity with the data of the literature (Bellier et al, 1995;Padilha et al, 1995;, the proportion of propionic acid (C3) was higher than that of butyric acid (C4) before weaning, but thereafter this became reversed, so that the ratio of the two fatty acids (C3 : C4) decreased from .1.0 to ,1.0. The increase of the butyrate concentration might be explained by an increase in some butyrate-producing bacteria.…”
Section: Discussionsupporting
confidence: 89%
“…In conformity with the data of the literature (Bellier et al, 1995;Padilha et al, 1995;, the proportion of propionic acid (C3) was higher than that of butyric acid (C4) before weaning, but thereafter this became reversed, so that the ratio of the two fatty acids (C3 : C4) decreased from .1.0 to ,1.0. The increase of the butyrate concentration might be explained by an increase in some butyrate-producing bacteria.…”
Section: Discussionsupporting
confidence: 89%
“…Most of the caecal changes occurred between 21 and 28 days, when the solid feed intake became significant irrespective of the nutritional status of young, weaned or suckling. As in the literature, VFA concentration increases then stabilises, mainly resulting from variations in acetate production (Padilha et al, 1995). A reduction of the propionateto-butyrate ratio (Padilha et al, 1995;Piattoni et al, 1995;, a decrease in minor VFA production (Padilha et al, 1995) and a decrease in pH (Padilha et al, 1995;Piattoni et al, 1995; are generally observed between 21 and 28 days of age.…”
Section: Discussionsupporting
confidence: 61%
“…As in the literature, VFA concentration increases then stabilises, mainly resulting from variations in acetate production (Padilha et al, 1995). A reduction of the propionateto-butyrate ratio (Padilha et al, 1995;Piattoni et al, 1995;, a decrease in minor VFA production (Padilha et al, 1995) and a decrease in pH (Padilha et al, 1995;Piattoni et al, 1995; are generally observed between 21 and 28 days of age. With respect to fibrolytic activities of caecal bacteria, we observed a peak for pectinolytic and xylanolytic activities on Figure 5 Changes in bacterial enzyme activities in the caecal content of rabbits according to their weaning age.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Whatever feed restriction, age or the group × age interaction, the caecal levels of total VFA or the VFA molar proportions were within the range of the values reported by Gidenne (1997) and García et al (2002). The VFA molar proportions differ significantly according to age, which is probably associated with the relationships among ages, intestinal microflora and fermentation parameter (Padilha et al, 1995). Moreover, some differences in VFA in the present study might be affected by the modification of feeding behaviour of the AL and restricted groups (Gidenne et al, 2012).…”
Section: Digestibility Of Nutrientssupporting
confidence: 54%